SOCIAL VARIATIONS OF LANGUAGE USER (EDUCATION, JOB, AND SOCIAL PRANATA) - Fadilla Oktaviana; Ina Rohiyatussakinah (Journal of English Language Teaching and Literature (JELTL), 2019)
This study aims to describe the social variation of language based on education level, type of work, and social institutions on Facebook users with an age range of 24-50 years. The source of data in this study is the status written on social media in this case facebook. The data collection technique is done by referring to the note taking technique. The data analysis technique used is content analysis. The results of the analysis show that the educational background, the type of work that is owned and the social institutions possessed by the users of the language are very influential in the content of writing, choice of words and writing when communicating. Although not a single factor because there are still many other factors that affect such as psychology, writing style, and others.